2006
DOI: 10.1108/14684520610650309
|View full text |Cite
|
Sign up to set email alerts
|

Web interface consistency in e‐learning

Abstract: Purpose -The purpose of this research is to examine the effects of interface consistency on the learning performance of skilled and novice computer users who are studying with web-based e-learning systems. Design/methodology/approach -A literature review was conducted, and an experiment was set up to collect data on learning performance with respect to interface consistency and e-learning systems. Statistical methods were applied. Findings -Skilled students made more errors than novices when using a physically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(49 citation statements)
references
References 26 publications
3
45
1
Order By: Relevance
“…The advanced usability of an elearning platform offered by a careful selection of colors can enhance students trust in the e-learning platform and the available content. Our conclusion follows Rhee, Moon and Choe (2005) results, showing that skilled students are generally more sensitive to interface consistency than novice students. The trust felt thanks to a proper assemblage of colors can enhance the appropriation of the e-learning platforms and help novices to become skilled, in order to perform more quickly and easily to exams.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…The advanced usability of an elearning platform offered by a careful selection of colors can enhance students trust in the e-learning platform and the available content. Our conclusion follows Rhee, Moon and Choe (2005) results, showing that skilled students are generally more sensitive to interface consistency than novice students. The trust felt thanks to a proper assemblage of colors can enhance the appropriation of the e-learning platforms and help novices to become skilled, in order to perform more quickly and easily to exams.…”
Section: Resultssupporting
confidence: 88%
“…Research has found color to be an important factor in e-commerce, influencing website aesthetics (Agarwal and Hedge, 2008;Coursaris et al, 2008;Schmidt and Liu, 2005) e-retailer perceptions (Agarwal and Hedge, 2008), user preference for e-commerce web sites (Lee and Koubek, 2010). With the interaction with the system, as well as the aesthetics of the interface being also of similar importance in the context of e-learning, it can be assumed that these works can imply a link between color and memorization and trust in e-learning, Color is one of the components that take part in the physical consistency (Rhee et al 2005). The physical consistency is part of the interface consistency of the e-learning platform.…”
Section: Effect Of Color On E-learningmentioning
confidence: 99%
See 1 more Smart Citation
“…It is designed to align with the government initiative in encouraging the use of IT in every aspect of life including education. Web-based education is applied to provide the course content, instruction and interactive communication between students and educators (Rhee et al, 2006).…”
Section: E-learningmentioning
confidence: 99%
“…In Rhee et al (2006), it is stated that the system operations must consider a lot of things to attain satisfaction of students. Interface consistency, interactivity and usability are the components affecting the satisfaction of the users.…”
Section: System Operations In E-learningmentioning
confidence: 99%